The Implementation of the Qur'an Reading and Writing Program at SD Rahmat Islamiyah Medan - Ina Zainah; Zainuddin Zainuddin (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to describe the implementation of the Qur'an Reading and Writing Program (BTQ) at SD Rahmat Islamiyah Medan, including its planning, execution, evaluation, as well as the supporting and inhibiting factors encountered in the process. This research employs a qualitative descriptive approach with data collection techniques comprising observation, interviews, and documentation. The subjects of this study include the school principal, Islamic Religious Education (PAI) teachers, and students. The findings reveal that the BTQ program at SD Rahmat Islamiyah Medan is implemented through a structured and systematic approach, utilizing the Iqra' method integrated into the school's daily learning activities. The program is supported by qualified teaching staff, adequate learning facilities, and strong parental involvement. However, several challenges remain, including the heterogeneous ability levels of students and limited instructional time allocation. The evaluation is conducted periodically through oral and written assessments. Overall, the BTQ program has demonstrated a significant positive impact on students' Qur'anic literacy and the development of their religious character.